Design and practices of Huizhou Zhuangyuan’s cultural and creative products based on narrative design - Zhao, Waner; Suhaily, S. Siti; Mansor, Azmi Bin (Edelweiss Applied Science and Technology, 2024)
This paper examines the design theories and practices of Huizhou Zhuangyuan cultural and creative products by combining narrative design methods with the theme cultural factors. It proposes a narrative design method model for Huizhou Zhuangyuan cultural and innovative products focusing on the narrative theme, path, reconstruction, and expression based on a comprehensive literature review, a market survey and consumer analysis. The findings confirmed the internal logic of the three points of designers, cultural and creative products, and consumers. It suggests that the typical Zhuangyuan culture resources, such as the Zhuangyuan Pavilion, Haiyang Academy, Zhuangyuan hats and costumes, and Zhuangyuan handwriting in Huizhou Zhuangyuan culture, are prototypes. It concludes that the cultural and creative products should be created around some narrative themes, including Zhuangyuan’s ideals of “studying hard and cultivating the character” and “striving for a rank and working for the country.”